Glucose addition in natural forest soils has higher biological nitrogen fixation capacity than other types of soils - Chen He; Kaikai Li; Lei Meng; Yunze Ruan; Zhongjun Jia (Scientific Reports)
Abstract Land use changes soil microbial and chemical properties, but the mechanism of biological nitrogen fixation under different land use patterns is rarely reported, so we used four types of soil: Natural forest soil (NS), healthy banana soil (HS), diseased banana soil (DS) and paddy soil (PS). Treatments included the control (CK), addition of glucose (G), addition of glucose and ammonium nitrate (GN), addition of banana straw (BS), addition of banana straw and ammonium nitrate (BSN), addition of banana root (BR), and addition of banana root and ammonium nitrate (BRN). The study found that the change of soil utilization types, glucose addition increased carbon dioxide emissions (Compared with the control, increased by 963.11%, 508.39%, 794.77% and 511.34%, respectively) and enhanced the ability of soil microbial nitrogen fixation. Importantly, natural forest soil microorganisms have a higher biological nitrogen fixation capacity compared to other types of soils. Glucose addition caused the accumulation of ammonium nitrogen (Compared with the control, increased by 426.08%, 934.21%, 420% and 1065.95%, respectively), indicating that microorganisms had higher utilization efficiency of soluble carbon and enhanced the biological nitrogen fixation capacity, and nitrogen addition caused the accumulation of ammonium nitrogen, thereby weakening the biological nitrogen fixation capacity. At the same time, glucose significantly increased the Fimicutes phylum (83.73%, 66.38%, 67.18% and 70.36%) and lowered the level of other bacterial phylums, thereby reducing the bacterial network structure, and the stability of the soil environment has decreased. Forest analysis showed that CO2 was an important factor in predicting the bacterial community structure of different soil types, an increase in CO2 content can predict drastic changes in the bacterial community. Bacteria at the Fimicutes phylum level preferred glucose, which may also have a negative effect on bacteria at the level of other phylums.